Clinical Value of Deep Vein Thrombosis Density on Lower-Extremity CT Venography: Prediction of Pulmonary Thromboembolism - Jung, Jae Hyeop; Kim, Jin Kyem; Kim, Taeho; Kim, Dong Kyu (Current Medical Imaging, 2024)
Aim Diagnosis of pulmonary thromboembolism (PTE) can be delayed if the signs and symptoms of patients are nonspecific. Introduction To assess the clinical value of deep vein thrombosis (DVT) density on computed tomography (CT) venography for predicting PTE. Methods From 2016 to 2021, patients with DVT diagnosed on lower-extremity CT venography were included. Of these patients, those without PTE were classified into ‘DVT-only group’ and those with PTE were classified into the ‘DVT with PTE group’. The DVT Hounsfield unit (HU) density was measured by drawing free-hand region-of-interests within the thrombus at the most proximal filling defect level. The risk factors associated with PTE were identified by using multivariate logistic regression analysis. A receiver operating characteristic (ROC) analysis was used to evaluate the value of DVT density for predicting the risk of PTE. Results and Discussion This study included 177 patients with a mean age of 41.7 ± 10.3 years (DVT-only group: 105 patients; DVT with PTE group: 72 patients). DVT density was significantly higher in DVT with the PTE group than DVT-only group (66.8HU ± 8.7 vs. 57.9HU ± 11.1, p < 0.001). The ROC analysis revealed that the area under the curve (AUC), sensitivity, and specificity for predicting the risk of PTE were 0.737, 72.2%, and 66.7%, respectively, at a DVT density cutoff of 63.0 HU. On univariate and multivariate analysis, DVT density was the only significant risk factor associated with PTE. Conclusion Higher DVT density was a significant risk factor for PTE. In addition, DVT density could be a predictive factor for PTE.
Keywords: Hounsfield unit